Application Of Claims For Payment In House Using Ate Seafood Larasatimu Visual Foxpro 9.0 - Anggar Prasetyo; Ire Puspa Wardhani, ir, mmsi (Jurnal Sistem Informasi, 2008)
Application claims payment in larasatimu seafood restaurant was created to facilitate the carrying out payment transactions so that payments be more effective and efficient.Claims for payment applications built using microsoft visual foxpro 9.0 for using microsoft visual foxpro 9.0 applications is made easy bill payments designed to utilize the various facilities provided by microsoft visual foxpro 9.0, so it is easy to use application.Keywords: applications, bill payment, visual foxpro 9.0